A mixed integer nonlinear programming approach for petroleum refinery topology optimisation - Albahri, Tareq A.; Khor, Cheng Seong; Elsholkami, Mohamed; Elkamel, Ali (Chemical engineering research & design, 2019)
•Proposed strategy to devise configuration then optimize conversion and temperature.•Implemented on case study of a real-world refinery in Kuwait.•Obtained resulting configuration that agrees with industrial practice. This work presents a mixed integer nonlinear programming (MINLP)-based superstructure optimisation approach to synthesize an optimal petroleum refinery topology or configuration for large-scale grassroots refinery systems. We develop a superstructure to include many possible prospective configurations and formulate rigorous models for the 32 commercial refinery processes that constitute the configurations, which gives rise to a convex MINLP model. The objective function is to maximize the total refinery profit for a given crude oil feed subject to material and energy balance constraints. We apply a two-level optimisation procedure: a master module to construct configurations from the superstructure and a submodule to optimize the process unit conversions and product temperatures of the configurations. A numerical example based on an actual operating refinery in Kuwait is illustrated to implement the approach with a resulting configuration that agrees with real-world practices.